Associations between use of antibiotic and non-antibiotic drugs on the gastrointestinal carriage of Klebsiella pneumoniae in a general adult population in Norway - Le, Truong An (UiT Norges arktiske universitet, 2021)
Antimicrobial resistance has long been a problem and a struggle to compromise as life-threatening infections are harder to treat. Among common pathogens, Klebsiella pneumoniae (K.pneumoniae) can be a highly resistant bacteria associated with increased mortality when infecting critically ill and immunocompromised patients. Prevalence of gastrointestinal carriage depends on several risk factors. Hospital stays and antibiotic use have been associated with K. pneumoniae carriage in the past, and several researchers have investigated how non-antibiotic drug use can alter the gut microbiome. Few have investigated non-antibiotic drug use as a potential risk factor. In this study we investigated if the use of antibiotic, non-antibiotic drugs and a combination of drugs can affect the gastrointestinal carriage of K. pneumoniae in terms of total exposure in defined daily dose (DDD), daily dosage and time of drug use. Our study population consisted of 2,997 participants aged ≥ 40 years from the seventh wave of the Tromsø Study: Tromsø 7 (2015-2016). Drug use data was acquired from the Norwegian Prescription Database (NorPD) and linked with data from Tromsø 7. We constructed treatment episodes with an allowed gap of 14 days and an assumption of 80% adherence and used logistic regression to analyze the different drugs as risk factors. We included the past six months for non-antibiotic and past two months for antibiotics in the analysis. Antacids (adjusted odds ratio 1.004, 95% Cl 1.001-1.006), antibiotics (1.027, 1.004-1.049), increasing age (1.016, 1.005-1.028), diabetes mellitus (2.467, 1.423-4.274) and Crohn’s disease/ulcerous colitis (2.367, 1.281-4.406) were factors based on total drug use exposure in DDD. As for daily dosage, antibiotics (1.949, 1.301-2.920), increasing age (1.018, 1.007-1.030) and having Crohn’s disease/ulcerous colitis (2.355, 1.271-4.363) were risk factors. We used a Venn diagram to illustrate the prevalence of carriage when a combination of drugs was used. The prevalence increased among those using ...